Comparing the Dimensional Accuracy of Casts Obtained from Two Types of Silicone Impression Materials in Different Impression Techniques and Frequent Times of Cast Preparation - Ali Hafezeqoran; Mahdi Rahbar; Roodabeh Koodaryan; Tina Molaei (International Journal of Dentistry)
Introduction. The dimensional accuracy of casts is essential in the quality of fixed prosthesis treatment, whereby the impression method is a very crucial factor affecting it. The aim of this in vitro study is to compare the dimensional accuracy of casts resulting from two types of silicone impression materials in different impression techniques and frequent times of cast preparation. Materials and Methods. A metal model was made from two prepared abutments, and 10 casts were prepared from each material technique (n = 40). The impressions were made by condensation and addition silicone (one-stage and two-stage impressions). The casts were made from same impressions 1 h, 24 h, and 14 days. The diameter, height, and the distance between two dies were recorded. Data were analyzed by repeated measure ANOVA (P value <0.05). Results. The dimensional accuracy of all four materials techniques of impression (diameter, height, and the distance between dies) was the same in different times of impression. Dimensional accuracy of the die diameter and distance between dies in one-stage (Speedex) condensation silicon and one-stage (Panasil) addition silicone did not differ significantly, and their one-stage method developed more accurate casts compared to the two-stage method of the same impression material. The height of the casts prepared from the one-stage method through Speedex and Panasil did not differ significantly from the two-stage method of the same impression material. Conclusion. One-stage condensation silicone and one-stage addition silicone material techniques offered the maximum dimensional accuracy in the obtained casts. The time of impression did not have any significant effect in the accuracy of any of the four impression material techniques.